SOSIALISASI MARAKNYA PROSTITUSI ONLINE DI INDONESIA SOCIALIZATION ON THE RISE OF ONLINE PROSTITUTION IN INDONESIA - Ikama Dewi Setia Triana; Eti Mul Erowati; Elisabeth Pudyastiwi (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2023)
This community service aims to provide knowledge and prevent the rise of online prostitution in Indonesia. Online prostitution is a problem that really threatens the younger generation and changes the culture of Indonesian society. Apart from having a bad effect on changing a good legal culture, online prostitution can become addictive for users. It takes good legal awareness to understand the damages caused by online prostitution. There are similarities between prostitution and drug cases. Both of these cases provide legal action for both drug dealers and their pimps. What makes the difference is that in narcotics cases, the user can be free from criminal law action with the condition that they are required to carry out the rehabilitation process until they recover from their addiction to the drug. As for prostitution cases, prostitutes and their service users are exempt from criminal acts with the condition that they "only" have to report to the police. In this case, there is a possibility that prostitution perpetrators will repeat their actions because they feel protected, as long as there are no regulations governing them.